The impact of human capital development on economic growth in Ethiopia: Evidence from ARDL approach to co-integration - Kidanemariam Gidey Gebrehiwo (College of education, Bahir Dar University, 2023)
The main objective of this study was to analyze the impact of human capital development on economic growth in Ethiopia. The methodology used in the study is ARDL Approach to Co-integration. The findings of the study indicate that there is a stable long run relationship between real GDP per capita, education human capital, health human capital, labor force, gross capital formation, government expenditure and official development assistance. The estimated long run model indicates that human capital in the form of health has big positive impact on real GDP per capita rise followed by education human capital. These findings are consistent with the endogenous growth theories. In the short run, the coefficient of the error correction term is -0.7366 suggesting about 73.66 percent annual adjustment towards long run equilibrium. The findings of this paper imply that an economic performance can be improved significantly when the ratio of public expenditure on health to GDP increases and when secondary school enrolments get better